2024
DOI: 10.1159/000536643
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Modifiable Risk Factors for Dementia and Mild Cognitive Impairment: An Umbrella Review and Meta-Analysis

Aaron Jones,
Muhammad Usman Ali,
Meghan Kenny
et al.

Abstract: Introduction The prevalence of mild and major neurocognitive disorders (NCDs), also referred to as mild cognitive impairment and dementia, is rising globally. The prevention of NCDs is a major global public health interest. We sought to synthesize the literature on potentially modifiable risk factors for NCDs. Methods We conducted an umbrella review using a systematic search across multiple databases to identify relevant systematic reviews and meta-analyses. Eligible reviews examined potentially modifiable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Prompt diagnosis could help in slowing the advancement of the disease, so identifying risk factors leading to MCI and its evolution into more severe neurocognitive disorders is crucial. Research has pinpointed several causative factors such as inadequate physical activity, alcohol consumption, smoking, substandard diet, social, environmental, and other factors [7]. Moreover, it was suggested that exposure to bisphenol A (BPA) may affect cognitive functions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Prompt diagnosis could help in slowing the advancement of the disease, so identifying risk factors leading to MCI and its evolution into more severe neurocognitive disorders is crucial. Research has pinpointed several causative factors such as inadequate physical activity, alcohol consumption, smoking, substandard diet, social, environmental, and other factors [7]. Moreover, it was suggested that exposure to bisphenol A (BPA) may affect cognitive functions [8].…”
Section: Introductionmentioning
confidence: 99%